Electrical status epilepticus in sleep: The role of thalamus in etiopathogenesis. (December 2021) - Kilic, Huseyin; Yilmaz, Kubra; Asgarova, Parvana; Kizilkilic, Osman; Hatay, Gokçe Hale; Ozturk-Isik, Esin; Yalcinkaya, Cengiz; Saltik, Sema
Highlights: Disturbances in thalamocortical interactions may play a role in electrical status epilepticus in sleep. Patients with ESES and normal magnetic resonance imaging have smaller relative thalamic volume. Decreased ratio of N-acetyl aspartate to creatine measured in magnetic resonance spectroscopy has been accepted as a sign of neuronal cell loss or dysfunction. In ESES patients the NAA/Creatine ratio was found to be significantly lower than the healthy control group. Abstract: Purpose: In patients diagnosed with epilepsy, decreased ratio of N-acetyl aspartate to creatine (NAA/Cr) measured in magnetic resonance spectroscopy (MRS) has been accepted as a sign of neuronal cell loss or dysfunction. In this study, we aimed to determine whether a similar neuronal cell loss is present in a group of encephalopathy with electrical status epilepticus in sleep (ESES) patients Methods: We performed this case-control study at a tertiary pediatric neurology center with patients with ESES. Inclusion criteria for the patient group were as follows: 1) a spike-wave index of at least 50%, 2) acquired neuropsychological regression, 3) normal cranial MRI. Eventually, a total of 21 patients with ESES and 17 control subjects were enrolled in the study. MRI of all control subjects was also within normal limits. 3D Slicer program was used for the analysis of thalamic and brain volumes. LCModel spectral fitting software was used to analyze single-voxel MRS data from the right and left thalamus of the subjects. Results: The mean age was 8.0 ± 1.88 years and 8.3 ± 1.70 years in ESES patients and the control subjects. After correcting for the main potential confounders (age and gender) with a linear regression model, NAA/Creatine ratio of the right thalamus was significantly lower in the ESES patient group compared to the healthy control group ( p  = 0.026). Likewise, the left thalamus NAA/Cr ratio was significantly lower in the ESES patient group than the healthy control group ( p  = 0.007). After correcting for age and gender, right thalamic volume was not statistically significantly smaller in ESES patients than in healthy controls ( p  = 0.337), but left thalamic volume was smaller in ESES patients than in healthy controls ( p  = 0.024). Conclusion: In ESES patients, the NAA/Creatine ratio, which is an indicator of neuronal cell loss or dysfunction in the right and left thalamus, which appears regular on MRI, was found to be significantly lower than the healthy control group. This metabolic-induced thalamic dysfunction, which was reported for the first time up to date, may play a role in ESES epileptogenesis.